Anti-Ma2–associated limbic encephalitis with coexisting chronic inflammatory demyelinating polyneuropathy in a patient with non-Hodgkin lymphoma: A case report. Issue 40 (October 2017) - Ju, Weina; Qi, Baochang; Wang, Xu; Yang, Yu
Abstract: Rationale: We report the rare case of a 74-year-old man with anti-Ma2–associated paraneoplastic neurologic syndrome (PNS), and review and analyze the clinical manifestations, diagnosis, and treatment of the disease. Patient concerns: The patient presented with a 5-month history of muscle weakness, progressive body aches, and weakness and numbness in both lower extremities. Before his hospitalization, he had experienced cognitive function decline; ptosis, inward gaze, and vertical gaze palsy in the right eye; and occasional visual hallucinations. Brain and spinal cord magnetic resonance imaging (MRI) yielded normal results. Anti-Ma2 antibodies were detected in both serum and cerebrospinal fluid. A 4-hour electroencephalogram showed irregular sharp slow waves and δ waves in the temporal region. Electromyography showed peripheral nerve demyelination. Positron-emission tomography/computed tomography (PET-CT) examination revealed hypermetabolism in the lymph nodes of the whole body. Biopsy of the lymph nodes showed non-Hodgkin lymphoma. Diagnosis: A clinical diagnosis of lymphoma and PNS was made. Interventions: The patient was treated with intravenous dexamethasone (15 mg/day) for 3 days. Lessons: We have presented a rare case of a PNS involving both the central and peripheral nervous systems. The clinical features of this case indicated anti-Ma2–associated encephalitis and chronic inflammatory demyelinating polyneuropathy. PET-CT played a critical role in enabling early diagnosis and prompt treatment in this case.